Organophotocatalytic or Electrophotocatalytic Reduction and Functionalization Reactions with a Thioxanthone-TfOH Complex Catalyst - Kang, Wen-Jie; Zhang, Yanbin; Guo, Hao (Synlett, 2024)
Thioxanthone has long been a prominent catalyst in the field of photocatalysis, owing to its high triplet energy and long triplet lifetime that render it suitable for energy transfer reactions. However, its low oxidation potential and short singlet lifetime have posed challenges when employing it for electron-transfer reactions. This account summarizes our efforts in developing a potent and long-lived thioxanthone-TfOH complex (9-HTXTF) catalyst, and its application in energy-demanding redox transformations such as organophotocatalytic or electrophotocatalytic reduction and functionalization reactions.1 Introduction2 Discovery and Properties of the Catalyst 9-HTXTF3 Organophotocatalysis4 Electrophotocatalysis5 Conclusion
Keywords: organophotocatalysis; electrophotocatalysis; 9-HTXTF; reduction; functionalization